Prevalence of Obesity and Some Related Attributes among Umm Al-Qura University Female Students in Makkah, Saudi Arabia - Abdelhafez, Amany Mokhtar; Mohammad, Salma Sa`ad (Pakistan Journal of Nutrition, 2013)
The prevalence of obesity is increasing worldwide at an alarming rate in both developing and developed countries. It has become a serious epidemic health problem, estimated to be the fifth leading cause of mortality at global level. This study was designed to determine the prevalence of obesity among students at Umm Al-Qura University in Makkah, Saudi Arabia and to investigate some of the epidemiologic risk factors contributing to it. A cross sectional study was conducted during the academic year 2009-2010. The study included 224 randomly selected students enrolled at Umm Al-Qura University. Data were collected using a pretested, structured self-administered questionnaire. Weight, height, waist hip ratio and Body Mass Index (BMI) were recorded for each student. Statistical analysis was done using SPSS version 16. The prevalence of overweight and obesity among the studied students was 25% (19.2%, were overweight and 5.8% were obese). Factors behind overweight and obesity were; high family monthly income, family history of obesity, eating while bored, depressed and upset. The association between physical activity, dietary factors and obesity were not observed in this study. Our findings suggest the need for strategies and coordinated efforts at all levels to reduce the tendency of overweight and obesity and to promote healthy eating habits in our youth.